The bumblebees of Gansu, Northwest China (Hymenoptera, Apidae) - An, Jiandong; Williams, Paul H.; Zhou, Bingfeng; Miao, Zhengying; Qi, Wenzhong (Zootaxa, 2011)
Bumblebees are important pollinators for agricultural and natural ecosystems. Gansu province, China, is located in part of the greatest hotspot of bumblebee diversity worldwide, a region of very varied geomorphology and vegetation. We report on a recent field survey of the bumblebees of Gansu made between 2007–2010. A sample of 5941 bumblebee specimens from Gansu are assigned to 49 species. Two older specimens held in London add two more species to this list. Together, these 51 species belong to 10 subgenera of the genus Bombus, and 10 species (nearly one fifth of the fauna) are recorded for the first time from Gansu: B. asiaticus, B. bicoloratus, B. chinensis, B. coreanus, B. deuteronymus, B. expolitus, B. festivus, B. grahami, B. hypocrita, and B. opulentus. None of the species is endemic to Gansu. We provide distribution maps and describe variation in local species richness and abundance and list the food plants used in Gansu. The highest bumblebee richness for the province is in the southeastern mountains and Qinghai-Tibetan plateau in the southwest. We describe how the fauna of Gansu is transitional between the fauna of North China and the fauna of the more southern Sichuan-Himalayan region.